2018
DOI: 10.1186/s13075-018-1691-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of bone erosions and enthesiophytes in the joints of patients with psoriasis or psoriatic arthritis - effects of age and disease duration

Abstract: BackgroundComprehensive simultaneous quantification of bone erosion and enthesiophytes in the joints of patients with psoriatic arthritis (PsA) has not been performed. Herein, we aimed to compare the extent of bone erosion and enthesiophytes in patients with PsA, psoriasis (PSO) and healthy controls, assess the influence of age and disease duration on the development of erosions and enthesiophytes and define their impact on physical function.MethodsPatients with PsA or with PSO and controls were analysed by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 25 publications
6
50
0
4
Order By: Relevance
“…Simon et al assessed the number and the size of erosions and enthesophytes in a cohort of 203 patients, showing that bone erosions depend on patient age and disease duration, whereas enthesophytes are less age dependent. 44 Kocijan et al showed that the duration of skin disease influences bone loss. 40 Moreover, Wu and colleagues, examining a cohort of 60 patients with PSA over an interval of 5 years, found an increase in terms of the volume of erosions and enthesophytes despite the treatment.…”
Section: Dual-energy X-ray Absorptiometrymentioning
confidence: 99%
“…Simon et al assessed the number and the size of erosions and enthesophytes in a cohort of 203 patients, showing that bone erosions depend on patient age and disease duration, whereas enthesophytes are less age dependent. 44 Kocijan et al showed that the duration of skin disease influences bone loss. 40 Moreover, Wu and colleagues, examining a cohort of 60 patients with PSA over an interval of 5 years, found an increase in terms of the volume of erosions and enthesophytes despite the treatment.…”
Section: Dual-energy X-ray Absorptiometrymentioning
confidence: 99%
“…Definitionsgemäß muss mindestens in einer Ebene die Unterbrechung der Kortikalis nachgewiesen werden, um die Erosion zuverlässig von einer subchondralen Zyste zu differenzieren [4,14]. Erosionen beginnen bei der RA typischerweise an den sogenannten bare areas und bei der PsA an den Insertionsstellen der Gelenkkapsel [24,30,31].…”
Section: Erosionenunclassified
“…B. Erosionen) und osteoproliferativen Veränderungen typisch. Diese Knochenneubildungen entstehen nicht wie bei der primären Arthrose in der Belastungszone der Gelenke, sondern vielmehr an der Insertionsstelle von Enthesen; sie werden daher auch als "Enthesiophyten" bezeichnet [30,37]. MR-morphologisch sind sie als kleine knöcherne Anbauten im periartikulären Enthesenverlauf nachweisbar.…”
Section: Osteoproliferationenunclassified
“…Psoriasis-Patienten ohne Anzeichen von muskuloskelettalen Symptomen, aber mit strukturellen enthesealen Läsionen, haben ein höheres Risiko, eine klinisch manifeste PsA zu entwickeln [4,9]. Diese strukturellen enthesealen Läsionen sind bei PsA-Patienten mit einer funktionellen Beeinträchtigung assoziiert [7]. Weitere CT-Studien an PsA-Patienten bewiesen, dass das Fortschreiten von Erosionen und strukturellen enthesealen Läsionen bei Patienten durch IL-17-Inhibition gehemmt werden kann [1, 2], und dass PsA-Patienten, die mit biologischen Disease Modifying Anti-Rheumatic Drugs (DMARDs) behandelt werden, von einer höheren Knochenmasse und einer besseren Knochenfestigkeit profitieren als PsA-Patienten, die nur MTX oder gar keine DMARDs erhalten [5].…”
Section: Computertomografie Bei Der Psoriasis-arthritisunclassified
“…Jedoch können CT-Forschungs ergebnisse einen wertvollen Beitrag zu einem besseren Verständnis der Krankheit sowie des Therapieansprechens leisten. Insbesondere Studien unter Verwendung der hochauflösenden peripheren quantitativen Computertomografie (HR-pQCT) waren hierbei in den letzten Jahren hilfreich [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
unclassified